Perceptions and attitudes of black men in a rural district of South Africa towards depression and its treatment - Hlabje C. Masemola; Saiendhra V. Moodley; Joyce Shirinde (South African Family Practice)
Background: Depression is a major contributor to the overall global burden of disease, impacting social life, family life and occupational functioning if left untreated. Despite its high prevalence and morbidity, the evidence suggests that men are hesitant to seek help, with a large percentage remaining undiagnosed. This study aimed to determine the attitudes and perceptions related to depression and its treatment amongst black men in a rural district of South Africa.